COMMUNITY SERVICE PROGRAM ON DEVELOPING DIGITAL ENGLISH TEACHING MODULES INTEGRATING LOCAL WISDOM FOR ELEMENTARY SCHOOL TEACHERS IN KEPAHIANG REGENCY: Community Service Program on Developing Digital English Teaching Modules Integrating Local Wisdom for Elementary School Teachers in Kepahiang Regency - Nurcholis, Ivan Achmad (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2025)
The community Service Program (PkM) aims to enhance the capacity of elementary school teachers in Kepahiang regency in developing digital English teaching modules that incorporate elements of local wisdom. this program is motivated by the limited availability of contextual teaching materials and the need to strengthen teachers’ digital literacy to support English instruction at the elementary level. the method employed involves participatory training through several stages, including needs assessment, workshops on digital module development, practice in designing materials based on Kepahiang local culture, as well as follow-up assistance through microteaching and classroom observations. the novelty of this program lies in the systematic integration of digital module development with local cultural content, making instructional materials more relevant, engaging, and accessible for both teachers and students. the results show that teachers gained a better understanding of module structure, appropriate selection of local cultural content, and ways to translate cultural elements into simple English suitable for young learners. the program also improved teachers’ confidence in using English in the classroom and encouraged more consistent language use through interactive digital activities. Although some teachers still face challenges related to vocabulary selection and grammatical accuracy, the availability of templates and guidelines helped them produce modules that are feasible for classroom use. overall, this program demonstrates that developing modules based on local wisdom combined with digital technology can enrich the learning process, strengthen teachers’ pedagogical and digital competencies, and offer strong potential for sustainability through ongoing collaboration and mentoring.